Creation of Nepal's First Skin Bank: Challenges and Outcomes. Issue 11 (November 2017) - Cai, Lawrence; Long, Chao; Karki, Bishal; Nakarmi, Kiran; Iqbal, Adnan; Casertano, Michele; Anderson, Sara; Patell, James; Chang, James; Rai, Shankar Man
Abstract : Background: In Nepal, burn trauma causes more than 55, 000 injuries each year. Burn-related mortality is high in Nepal, in part due to lack of allograft, leading to high infection rates. To address this challenge, our collaboration between Kirtipur Hospital, America Nepal Medical Foundation, Stanford University, and ReSurge International established Nepal's first skin bank. Methods: We identified 3 major tasks to create a sustainable skin banking program: 1) identify and acquire the equipment and personnel needed to collect, process, store, and graft cadaveric skin for burn injuries; 2) develop safe donation protocols and documentation tools that remain feasible for low-resource settings; and 3) develop a long-term awareness program to educate the Nepali people on skin donation, a previously foreign concept. Results: Kirtipur Hospital acquired the necessary equipment and materials for the skin bank through a combination of local and international fundraising efforts. Existing U.S. skin banking protocols were adapted for the Nepali setting and piloted on potential patients, donors, and physicians. For the first time in the hospital's history, patients with > 40% total body surface area burns were successfully treated with extensive allografts. Conclusions: It is feasible to create a skin bank in a country with no tradition of allograft skin use. Long-term sustainability now depends on spreading awareness and education in the Kathmandu Valley to overcome religious and cultural barriers that have hindered donor recruitment. Our low-cost and high-impact skin bank provides a model to expand this system to other hospitals both within Nepal and beyond. Abstract : Supplemental Digital Content is available in the text.